Peningkatan Mutu dan Strategi Pemasaran Digital PT Givo di Era Modern - Haniyah Zalsy; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2026)
The purpose of this study was to determine how entrepreneurship training impacts higher levels of creativity in students who participate in the Independent Entrepreneurship Program. This program is a national initiative that offers students practice-based entrepreneurship training through workshops, internships in MSMEs, start-up acceleration, pitching proposals, and expos. This study uses a qualitative descriptive case study approach that looks at activities carried out at the Muhammadiyah University of Surakarta. The results show that the training provided is able to improve students' understanding of entrepreneurship, team skills, business idea development, and the author's confidence in managing and marketing products. In particular, activities in the Luscious Parfum personalized perfume business project can provide students with experience in making decisions, conducting market analysis, and making decisions. Challenges such as budget constraints and market competition were successfully overcome through the use of social media and creative promotional strategies.